Inconsciente, palabra e imagen. Reflexiones sobre el uso del dibujo en la clínica (2013)
ABSTRACT: Based on the concepts and theories of Freudian Psychoanalysis, linguistics of F. Saussure and Structuralist semiology of Roland Barthes, it is described and analyzed some of the main differences and similarities between the systems of significance composed of linguistic and iconic signifiers. The unconscious and the drawing are articulated with the properties of language, such as the arbitrariness and the multivocity of the linguistic sign, the unique uses and significant social consensus, showing the radical difference of the image and the word with regard to the linear arrangement of set of signs and their discrete nature. It is argued that in clinical work pictures and words have a cooperative relationship rather than an exclusion one, questioning the idea that in psychoanalysis the use of various means to the word, such as drawing, represents a technical deviation.